Utilization of exterior surface dimples for stream-wise force reduction for a circular cylinder in cross-flow - Wu, M (2010)
Applying dimples on spherical bluff bodies have been found to be a major technique to control the surface flow and reduce the stream-wise force. However, not much work has been done on dimple applications on cylindrical Objects . This research project aims to investigate, firstly, whether the stream-wise force on a circular cylinder could be reduced by using dimples on its outer surface. Secondly, if it could, whether there is an optimum design that gives the biggest force reduction. Thirdly, what the roles of different approaches in this project might be? In order to find answers to these questions, experimental and computational methods have been used. One smooth and three dimpled cylinders have been tested. It was found that applying dimples on the outer surface of a cylinder is very effective in reducing stream-wise force. Drag coefficient significantly reduced by 17% to 48% depending on different Reynolds numbers. However, the dimpled design did not seem to be the key factor of the reduction, and the level of drag reduction was found to be insensitive to different dimpled patterns. Furthermore, it has also been found that CFD method would not be suitable as the research tool for this project because of its demanding requirement in computer power. Therefore, rig tests remained the primary method for this project. In addition, flow visualization technique was also used to show the wake region behind both the smooth and dimpled cylinders. It was clear that a smaller wake was associated with the dimpled case, which resulted in the pressure drag on the dimpled cylinder being smaller than for the smooth cylinder.